2020
DOI: 10.1038/s41598-020-63290-3
|View full text |Cite
|
Sign up to set email alerts
|

SOX3 promotes generation of committed spermatogonia in postnatal mouse testes

Abstract: SOX3 is a transcription factor expressed within the developing and adult nervous system where it mostly functions to help maintain neural precursors. Sox3 is also expressed in other locations, notably within the spermatogonial stem/progenitor cell population in postnatal testis. Independent studies have shown that Sox3 null mice exhibit a spermatogenic block as young adults, the mechanism of which remains poorly understood. Using a panel of spermatogonial cell marker genes, we demonstrate that Sox3 is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Recently, Sohlh1 is shown to regulate meiotic gene expression ( Sycp1 , Sycp3 ) by directly binding to their proximal promoters 45 . Sox3 is expressed exclusively in spermatogonia committed to differentiation 46 , and loss of Sox3 impairs early meiosis, including a downregulation of Sycp3 expression in young adult testes 47 . Thus, these data suggest that nutrient restriction induces a distinct network of TFs to complement RA signaling in the meiotic gene activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sohlh1 is shown to regulate meiotic gene expression ( Sycp1 , Sycp3 ) by directly binding to their proximal promoters 45 . Sox3 is expressed exclusively in spermatogonia committed to differentiation 46 , and loss of Sox3 impairs early meiosis, including a downregulation of Sycp3 expression in young adult testes 47 . Thus, these data suggest that nutrient restriction induces a distinct network of TFs to complement RA signaling in the meiotic gene activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While these genes comprised only 0.4% of expressed protein-coding genes in undifferentiated spermatogonia (53 of 13,497 expressed genes), they represented 1.1% of DAZL targets (29 genes of 2,633 DAZL targets), representing an enrichment of spermatogonial factors ( Figure 2D ; one-tailed hypergeometric test; p=1.71×10 −8 ). Two of these DAZL-targeted factors, Lin28a and Sox3 , promote the formation and proliferation of progenitor spermatogonia ( Chakraborty et al, 2014 ; McAninch et al, 2020 ) and may contribute to the diminished progenitor population observed in the Dazl cKO ( Figure 2E ). Additional factors, such as Foxo1 , Kit , Rarg , and Sall4 , promote spermatogonial differentiation ( de Rooij et al, 1999 ; Gely-Pernot et al, 2012 ; Goertz et al, 2011 ; Hobbs et al, 2012 ; Yoshinaga et al, 1991 ), consistent with the reduced spermatogonial differentiation in the Dazl cKO ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Progenitors exhibited activity of RARγ, SOX3 and SALL1. SOX3 and RARγ play key roles in SSC differentiation priming, validating cluster identity 38 , 39 . Proliferative SSC clusters were regulated by similar transcription factors including EGR3, HES1, HIF1A and DMRT3 while transitional A undiff were distinguished by activity of E2F7, E2F2 and EZH2 regulons.…”
Section: Resultsmentioning
confidence: 68%